2021
DOI: 10.1111/jcal.12568
|View full text |Cite
|
Sign up to set email alerts
|

Using eye movement modelling examples to guide visual attention and foster cognitive performance: A meta‐analysis

Abstract: Eye movement modelling examples (EMME) are computer‐based videos displaying the visualized eye gaze behaviour of a domain expert person (model) while carefully executing the learning or problem‐solving task. The role of EMME in promoting cognitive performance (i.e., final scores of learning outcome or problem solving) has been questioned due to the mixed findings from empirical studies. This study tested the effects of EMME on attention guidance and cognitive performance by means of meta‐analytic procedures. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 55 publications
3
21
0
Order By: Relevance
“…For example, empirical research has shown that the instructor’s image facilitates the learning of declarative knowledge but interferes with procedural knowledge (Hong et al, 2018 ). A recent meta-analysis has also shown that visual cues were most beneficial to learning performance when non-procedural tasks were taught in instructional videos (Xie et al, 2021 ). Practitioners need this contextual information to determine the boundary conditions for video design principles to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…For example, empirical research has shown that the instructor’s image facilitates the learning of declarative knowledge but interferes with procedural knowledge (Hong et al, 2018 ). A recent meta-analysis has also shown that visual cues were most beneficial to learning performance when non-procedural tasks were taught in instructional videos (Xie et al, 2021 ). Practitioners need this contextual information to determine the boundary conditions for video design principles to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Such visualizations, also known as gaze displays (see Figure 1) have been suggested to provide a promising tool for education (Jarodzka et al, 2017; van Gog, Kester, et al, 2009; Van & Scheiter, 2010). For instance, it has been shown that displaying the gaze of a teacher to learners in eye movement modelling examples enhances learning on a variety of tasks compared to regular video modelling examples without the gaze displayed (e.g., Chisari et al, 2020; Jarodzka et al, 2012; Mason et al, 2015; Van Gog et al, 2009; for a meta‐analysis see Xie et al, 2021). It has also been proposed that displaying the gaze of a learner back to them as a cue could improve monitoring accuracy (van Gog et al, 2009).…”
Section: Gaze Displaysmentioning
confidence: 99%
“…EMMEs are computer-based videos that display the gaze behaviour of a domain expert while they execute a problem-solving task. This is a training model, where (relative) novices learn from the experts using EMME as an instructional document (Xie et al, 2021). EMME video examples are professional vision (or the layover of the experts' visual focuses) simultaneously supplemented by the verbal explanations of the expert for complex real-life problems to be dissected and explained following the cognitive processes of the expert.…”
Section: Theories Applied In Eye-tracking Researchmentioning
confidence: 99%